Competitiveness, Income Distribution, and Growth in the Philippines: What Does the Long-run Evidence Show? - Jesus Felipe; Grace C. Sipin (Asian Development Bank (ADB), 2004)
This paper considers unit labor costs (ulcs), i.e., the ratio of the wage rate to labor productivity, as the indicator of competitiveness in the Philippines. It is shown that ulcs have an interpretation from the point of view of the functional distribution of income (i.e., the distribution of output between labor and capital). The paper documents the dynamics of the labor share in national income for 1980-2002, and provides an analysis of the long-run performance of the Philippine economy. The most salient features are: (i) decreasing wage rate (until the mid-1990s) and labor share; (ii) stable profit rate and increasing capital share: (iii) stagnant capital-labor ratio; (iv) decreasing capital productivity; (v) decreasing labor productivity (until the mid-1990s); and (vi) increasing markup, the latter interpreted as an indicator of the firms' capacity to enforce a certain claim on profits against laborers and competitors, or as an index of the capacity of firms to exert anticompetitive practices. It is argued that these characteristics indicate that the country is submerged in a "low-level equilibrium trap." This situation has profound implications for long-run growth and for the potential growth rate of the country, and explains the progressive deterioration of the Philippines during the last two decades, although some signs of recovery can be discerned.
hdl:11540/1910
Keywords: 330; Internationaler Wettbewerb; Lohnstückkosten; Arbeitsproduktivität; Kapitalproduktivität; Funktionelle Einkommensverteilung; Wirtschaftswachstum; Philippinen